Identification of the M-ring protein of the flagellar motor of Salmonella typhimurium. - Homma, M (1987)
The M ring is a substructure of the flagellar basal body of bacteria, which lies in the cytoplasmic membrane and is therefore close to the site where the energy of the transmembrane proton potential is converted into mechanical work of rotation of the motor. The protein from which this ring is constructed has not been identified. Flagellar hook-basal body complexes from Salmonella typhimurium were used as the immunogen for the preparation of monoclonal antibodies. An antibody obtained was directed against a major basal-body component, a 65-kDa protein that from mutant studies has been assigned as the product of the flaAII.1 gene. By immunoelectron microscopy, the antibody was observed to bind the innermost feature of the basal body: the cytoplasmic-facing surface of the M ring. We conclude that the 65-kDa protein is a component--probably the main component--of this important substructure of the flagellar motor.